The influence of traditional religion on fertility regulation among the kassena-nankana of northern Ghana - Adongo, P.B.; Phillips, J.F.; Binka, F.N. (My University, 1998)
This article presents findings from a study of the influence of traditional religion on reproductive preferences of Kassena-Nankana lineage heads in northern Ghana. Seven reproductive preference questions were administered to nine lineage heads who are primary practitioners of the cult of sooth-saying. With the assistance of soothsayers, interviews were repeated in conjunction with the invocation of religious rites in order to determine the views of ancestral spirits on the seven questions. Pairs of lineage head and ancestral interviews are compared to determine the role of traditional religion in shaping male reproductive preferences. Interview pairs reflect a shared preference for sons, large compounds, and a growing lineage. Findings nonetheless show that some ancestral spirits want small families, some even wanting fewer children than corresponding lineage heads. Spiritual consultations are nondogmatic and open to external ideas and influences, suggesting that family planning introduction will not encounter systematic religious opposition among the Kassena-Nankana.